Habitat type drives the distribution of non‐indigenous species in fouling communities regardless of associated maritime traffic. Issue 1 (15th October 2019) - Leclerc, Jean‐Charles; Viard, Frédérique; González Sepúlveda, Elizabeth; Díaz, Christian; Neira Hinojosa, José; Pérez Araneda, Karla; Silva, Francisco; Brante, Antonio
Abstract: Aim: Biological invasions and changes in land and sea use are among the five major causes of global biodiversity decline. Shipping and ocean sprawl (multiplication of artificial structures at the expense of natural habitats) are considered as the major forces responsible for marine invasions and biotic homogenization. And yet, there is little evidence of their interplay at multiple spatial scales. Here, we aimed to examine this interaction and the extent to which the type of artificial habitat alters the distribution of native and non‐indigenous biodiversity. Location: Southeast Pacific—Central Chilean coastline. Methods: Settlement plates were deployed upon two types of artificial habitats (floating and non‐floating hard substrates) at a total of ten study sites, exposed to either international or local traffic. After colonization periods of 3 and 13 months, plates were retrieved to determine their associated fouling sessile assemblages at an early and late stage of development, respectively. Putative confounding factors (temperature, metal concentrations) were taken into account. Results: While traffic type had no detectable effect, there were strong differences in community structure between habitats, consistent across the study region. These differences were driven by non‐indigenous species which contributed to 58% and 40% of the community structure in floating habitats after 3 and 13 months, respectively—roughly 10 times greater than in their non‐floating counterparts. Assemblages on floating structures also displayed a lower decline in similarity with increasing distance between sampling units, being thus more homogenous than non‐floating habitats at the regional scale. Main conclusions: With the absence of international traffic effect, the colonization success by non‐indigenous species appears to be mainly habitat‐dependent and driven by local propagules. Floating structures not only provide specific niches but characteristics shared with major introduction and dispersal vectors (notably hulls), and in turn constitute important corridors to invasions and drivers of biotic homogenization at multiple scales.